Judicial conflict and consensus : behavioral studies of American appellate courts - Lamb, Charles M.; Goldman, Sheldon (University Press of Kentucky, 1986)
These original essays by major scholars of judicial behavior explore the frequency, intensity, and especially the causes of conflict and consensus among judges on American appellate courts. Together, these studies provide new insights into judges' attitudes and values, role perceptions, and small group interactions.